2017
DOI: 10.1002/aoc.4199
|View full text |Cite
|
Sign up to set email alerts
|

Visible light driven amide synthesis in water at room temperature from Thioacid and amine using CdS nanoparticles as heterogeneous Photocatalyst

Abstract: Highly efficient photocatalytic thioacid mediated amide synthesis at room temperature using CdS nanoparticles as photocatalyst was observed under a household 30 W CFL in water. The operationally mild reaction was tolerant to a number of functional group substitutions on amine and could be scaled up to gram. This heterogeneous photocatalyst was extremely stable and could easily be recovered by simple centrifugation for at least six recycling reactions without any significant loss of catalytic performance. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…Photocatalytic synthesis of amide by CdS had been realized in water at room temperature under 30 W CFL lamp irradiation, giving 73-97 % yields of amides (Scheme 6b). [28] Surprisingly, the procedure can even take place in relatively moderate sunlight irradiation and a gram scale reaction was performed with a yield of 88 % under standard conditions. It has been reported that metal sulfides can facilitate the formation of CÀ C bonds as a photocatalyst.…”
Section: Binary and Ternary Metal Sulfidesmentioning
confidence: 99%
“…Photocatalytic synthesis of amide by CdS had been realized in water at room temperature under 30 W CFL lamp irradiation, giving 73-97 % yields of amides (Scheme 6b). [28] Surprisingly, the procedure can even take place in relatively moderate sunlight irradiation and a gram scale reaction was performed with a yield of 88 % under standard conditions. It has been reported that metal sulfides can facilitate the formation of CÀ C bonds as a photocatalyst.…”
Section: Binary and Ternary Metal Sulfidesmentioning
confidence: 99%
“…Finally, on the basis of the above control experiments and previous reports, plausible mechanisms are proposed for the formation of amide bonds by spontaneous and electrosynthetic reactions. In the process of spontaneous reaction (Scheme ), the ionization equilibrium of thiobenzoic acid ( 1 ) in EtOAc results in the presence of thiobenzoate anion ( 1‐A ) and a proton.…”
Section: Figurementioning
confidence: 53%
“…The resultso ft hese control experiments indicate that the formation of disulfide intermediates is criticalf or both spontaneous and electrosynthetic reactions. Finally,o nt he basis of the above controle xperiments and previousr eports, [12,13] plausible mechanismsa re proposed for the formation of amide bonds by spontaneous and electrosynthetic reactions. In the process of spontaneous reaction (Scheme 6), the ionization equilibrium of thiobenzoic acid (1) in EtOAc resultsi nt he presence of thiobenzoate anion (1-A) and ap roton.…”
mentioning
confidence: 72%
See 2 more Smart Citations